An adaptation strategy to urban heat: hospital rooms with radiant cooling accelerate patient recovery. Issue 3 (31st August 2021) - Hoffmann, Christina; Liebers, Uta; Humbsch, Philipp; Drozdek, Marija; Bölke, Georg; Hoffmann, Peter; Holzgreve, Adrien; Donaldson, Gavin C.; Witt, Christian
Background: Patients with respiratory diseases are vulnerable to the effects of heat. Therefore, it is important to develop adaptation strategies for heat exposure. One option is to optimise the indoor environment. To this end, we equipped hospital patient rooms with radiant cooling. We performed a prospective randomised clinical trial to investigate potentially beneficial effects of the hospitalisation in rooms with radiant cooling on patients with a respiratory disease exacerbation. Methods: Recruitment took place in June, July and August 2014 to 2016 in the Charité – Universitätsmedizin Berlin, Germany. We included patients with COPD, asthma, pulmonary hypertension, interstitial lung disease and pneumonia. 62 patients were allocated to either a standard patient room without air conditioning or a room with radiant cooling set to 23°C (73°F). We analysed the patients' length of stay with a Poisson regression. Physiological parameters, fluid intake and daily step counts were tested with mixed regression models. Results: Patients hospitalised in a room with radiant cooling were discharged earlier than patients in standard rooms (p=0.003). The study participants in chambers with radiant cooling had a lower body temperature (p=0.002), lower daily fluid intake (p<0.001), higher systolic blood pressure (p<0.001) and an increased daily step count (p<0.001). Conclusion: The results indicate that a radiant cooling system in hospital patient rooms provides clinical benefits for patients with respiratory disease exacerbations during the warm summer months, which may contribute to an earlier mobilisation. Radiant cooling is commended as a suitable adaptation strategy to reduce the clinical impact of climate warming. A radiant cooling system in hospital patient rooms provides clinical benefits for patients with respiratory disease exacerbations during summertime. Patients hospitalised in rooms with air convection free radiant cooling are discharged earlier. https://bit.ly/3p9Fkqm